PERAN EMPLOYEE AGILITY DAN EMPLOYEE ENGAGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN DI KARAWANG - Marhisar Simatupang; Lania Muharsih; Nur Ainy Sadijah; Randwitya Ayu Ganis Hemasti; Ahmad Paisal Gozali; Kurnia Pratiwi (LPPM Institut Pendidikan Nusantara Global, 2023)
The behavior of employees at work determines the success or failure of the company in achieving the vision and mission that has been set. Increasingly high business competition requires quality human resources, totality and agility in work. This study aims to determine the role of employee agility and employee engagement on organizational citizenship behavior among employees in the Employee District. The sample used in this study were 92 employees and the sampling technique used was snowball sampling. The scale used is the Psychology scale which consists of organization citizenship behavior, employee agility and employee engagement scales. Data analysis used SPSS software version 26. The results of the study found that there was an effect of employee agility and employee engagement on organizational citizenship behavior among employees in Karawang.